FAKTOR PENDORONG, PROSES DAN TANTANGAN TRANSFORMASI DIGITAL PADA USAHA MIKRO, KECIL DAN MENENGAH: TINJAUAN PUSTAKA SISTEMATIS - Ficky Eriyanto Triyudian Rasid; Sasongko Pramono H; Muhammad Nur Rizal (Informasi Interaktif, 2021)
As one of the backbones of the economy, Micro, Small and Medium Enterprises (MSMEs) aim to grow and develop their businesses in order to build a national economy based on just economic democracy. In various countries, MSMEs play an important role in job creation, productivity and economic growth. For the sake of sustainability and competitive advantage in MSMEs in this industrial era 4.0, digital transformation needs to be implemented. This paper aims to study the ongoing digital transformation of MSMEs in order to gain a richer understanding of the drivers, processes and challenges of digital transformation. There are 40 recent studies on digital transformation in MSMEs from 2016 to 2020 in the form of systematic literature reviews. The results of the study conducted were that MSMEs had different factors, processes and challenges according to the characteristics of each SMEs. The results of the research are practically an informative indicator for policy makers, information service providers, researchers and SMEs to evaluate the elements of digital transformation that have been running on MSMEs. Keywords: Digital Transformation, SMEs, MSMEs